A Menezes Vanstone Cryptosystem - Santoso, Kiswara Agung (Majalah Ilmiah Matematika dan Statistika, 2015)
Many kinds of cryptosystem models we have known. Generally if input of plaintext is alphabet so ciphertext is alphabet or real number that can be transform to alphabet. This paper will introduce a type of cryptosystem that have special output. It model is Menezes Vanstone cryptosystem. The plaintext of its method is pair of real number and ciphertext was produced is pair of real number too. If we want to know the meaning of ciphertext have to transform from real number to alphabet.